Limited soil carbon storage under long‐term organic fertilization in solar greenhouses. (28th June 2022) - Zhang, Yueqi; Hagedorn, Frank; Guidi, Claudia; Yang, Lijuan
Abstract: Environmental conditions, fertilization systems and cultivation practices in greenhouses differ from those in arable soil. Despite being a widespread intensive management practice, large uncertainties exist on the effects of long‐term fertilization on soil organic carbon (SOC) in greenhouse cultivation. The objective of this study was to explore the effects of 11‐year‐long fertilization on carbon (C) stocks in soil aggregates (>2 mm; 2–0.25 mm; 0.25–0.053 mm; <0.053 mm) and SOC fractions (free light fraction (free LF), intra‐aggregate particulate organic carbon (iPOC), mineral‐associated organic carbon (mAOC)) at 0–20 cm and 20–40 cm depth in a solar greenhouse. Five treatments were examined: control (no fertilizer), chicken manure (M), chicken manure plus straw (M + S), chicken manure plus lime (M + Ca), chicken manure plus straw and lime (M + S + Ca). Over the 11 years of continuous intensive organic fertilization, SOC contents of all fertilization treatments first increased sharply and then stabilized after 5 years. The M + S + Ca treatment increased the proportion of aggregate masses, SOC concentrations as well as SOC stocks of soil aggregates >2 mm, 2–0.25 mm, but straw or lime application alone had no significant effects. The M + S + Ca treatment increased the SOC stock of free LF, fine iPOC, coarse iPOC and mAOC by 97%, 38%, 22% and 25% compared with the M treatment, respectively. Straw treatment alone only significantly increased the soil labile C stock (free LF, iPOC). At 0–40 cm depth, the regression between the C stock and the C input had the steepest slope in bulk soil (slope = 0.223, R 2 = 0.87**). After 11 years, about 15% of the C inputs were sequestered in the soils. As the mAOC remained largely unaffected, the increase in SOC seems only short‐lived and reaches a new equilibrium within a few years when C inputs are balanced out by mineralization. Consequently, the intensive fertilization and management practices in greenhouse cultivation allowing obtaining high tomato yields results in an overall negative C balance.